Design And Development Of An Android-Based Nutrition Education And Stunting Prevention Information System For Pregnant Women (Case Study Sekotong Community Health Center) - Rifqi, Muhammad Ari; Sri Endang Anjarwani; Ari Hernawan (Informatics Engineering Dept., Faculty of Engineering, University of Mataram, 2023)
Malnutrition and stunting are serious issues in Indonesia, particularly in Sekotong Subdistrict, West Lombok Regency, West Nusa Tenggara. The prevalence of stunting in this subdistrict reached 94 cases in 2020. This research aims to develop an Android application called Yess Nutrition as a medium for educating pregnant women about nutrition and stunting prevention in Sekotong Subdistrict. The Design Thinking and Personal Extreme Programming methods are employed in the development of this application. The test results show that the application received a mean opinion score of 4.173, indicating good quality and user interface. It is expected that the Yess Nutrition app will enhance the knowledge of pregnant women regarding nutrition and stunting prevention. By leveraging the vast potential of the Android platform, this application has the potential to become an effective educational tool for raising awareness about nutrition and preventing stunting.